2010
DOI: 10.21608/jacb.2010.90073
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impacts of Environmental Conditions, Polyphenolic Compounds and Trypsin Inhibitor Against Ear and Kernel Rots Diseases of Maize

Abstract: Visible ear rot infection (VER), frequency of associated fungi percentages and disease severity rating (DSR) of 25 maize genotypes were affected significantly by the two years . Diseases criterion were higher in the season of 2008 than 2009. VER recorded 26.67 to 46.66% and 3.00 to 11.00% , DSR were ( 5) and (3-4) during the two seasons, respectively, with the most infected maize ones. VER caused significant reduction of yield weight (100 kernels/ g) with most of tested maize genotypes. Fusarium verticillioids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Concerning dough development time (mixing time), arrival time and weakening dough increased with increasing the addition amount of corn flours. These results are in the same trend with Hegazy (2002), Rizk (2004) and Farahat et al (2010), they found that, the wheat/maize doughs containing either 15 or 20% maize flour showed lower water absorption, mixing time and dough stability as compared to control dough. Dough weakening degrees increased from 100 for control to 110 and 120 BU.…”
Section: Rheological Properties Of Doughsupporting
confidence: 87%
See 1 more Smart Citation
“…Concerning dough development time (mixing time), arrival time and weakening dough increased with increasing the addition amount of corn flours. These results are in the same trend with Hegazy (2002), Rizk (2004) and Farahat et al (2010), they found that, the wheat/maize doughs containing either 15 or 20% maize flour showed lower water absorption, mixing time and dough stability as compared to control dough. Dough weakening degrees increased from 100 for control to 110 and 120 BU.…”
Section: Rheological Properties Of Doughsupporting
confidence: 87%
“…Many research groups have validated the role of plant trypsin inhibitor (TI) as mean of plant defense against fungal infection (Baker et al, 2009). Chen et al (2007) and Farahat et al (2010) detected that, antifungal trypsin inhibitor proteins was higher in resistant maize lines compared with susceptible ones and caused decreasing of infection by ear rot and associated fungi especially F. moniliforme. TI demonstrated antifunal activity against fungal growth and conidial germination of eight phytopathogenic fungi including F. moniliforme, may be partially due to its inhibition of fungal αamylase activity and production (Chen et al, 1999), limiting the avialibility of simple sugars needed for fungal growth and aflatoxin production (Woloshuk et al, 1997).…”
Section: Total Phenolics Antioxidant Activity Trypsin and α-Amylasementioning
confidence: 99%